Rhodomyrtus Tomentosa: A Phytochemical and Pharmacological Review - Hazrulrizawati, Hamid; Zeyohannes, Senait Sileshi; M. M., Yusoff (Innovare Academic Sciences Pvt Ltd, 2017)
Rhodomyrtus tomentosa is a common wood, prevalent in areas with undemanding soil conditions and resistant toward pests and diseases. The plant can be found in China, Taiwan, Philippines, Malaysia, Indonesia, and Vietnam. Literature and artwork indicate that R. tomentosa played an important holistic role in the daily lives of several ancient cultures, providing medicinal benefits. R. tomentosa exhibits a wide spectrum of pharmacological effects and has been used to treat colic diarrhea, wounds, heartburn, abscesses, gynecopathy, and as a pain killer. R. tomentosa was used in traditional Chinese medicine to treat urinary tract infection. 42 compounds have been isolated from this plant and structurally elucidated. They comprise phloroglucinol, flavonoid, terpenoid, anthracene glycoside, tannin, and other compounds. Rhodomyrtone, a member of the acylphloroglucinols demonstrated a significant activity against a wide range of Gram-positive bacteria. Rhodomyrtone exhibited both antimicrobial and anti-infective activities. Several biological activities have been documented as antibacterial, antifungal, antimalarial, osteogenic, antioxidant, and anti-inflammatory. R. tomentosa has been studied extensively for alternative antimicrobial agents. Although rhodomyrtone exhibited potential activity with a very low minimum inhibitory concentration value, the mechanisms of action of this compound are still unclear. Furthermore, toxicity studies on it extract to validate pharmacological activities are required.